Listening after nature : field recording, ecology, critical practice / Mark Peter Wright. - Wright, Mark Peter (Bloomsbury Academic, 2023)
'Listening After Nature' examines the constructions and erasures that haunt field recording practice and discourse. Analyzing archival and contemporary soundworks through a combination of post-colonial, ecological and sound studies scholarship, Mark Peter Wright recodes the Field; troubles conceptions of Nature; expands site-specificity; and unearths hidden technocultures. What exists beyond the signal? How is agency performed and negotiated between humans and nonhumans? What exactly is a field recording and what are its pedagogical potentials? These questions are operated by a methodology of listening that incorporates the spaces of audition, as well as Wright's own practice-based reflections.